Development of E-LKM Multicultural Education Based on Case Method as a Student Learning Resource - Nisa’u Rifka Latiffah; Ervan Johan Wicaksana; Dara Mutiara Aswan (Postgraduate, University of Mataram, 2025)
This study aimed to develop an electronic student worksheet (e-LKM) based on the case study method for the Multicultural Education course, focusing on multicultural education issues in Indonesia. The study was conducted due to students’ difficulties in understanding the material caused by limited interactive and accessible learning resources. This research employed a Research and Development (R&D) method using the 4D development model, consisting of define, design, develop, and disseminate stages. The developed e-LKM includes instructional materials, contextual case studies, videos, supporting articles, and higher-order thinking skills (HOTS) questions at the C4 and C5 levels. Canva and Flip PDF Professional were used to support interactivity and visual appeal. The feasibility of the e-LKM was evaluated through validation by subject-matter experts and media experts, assessments by the course lecturer, and student responses. The validation results indicated that the case study–based e-LKM was categorized as highly feasible in terms of content quality, language, visual design, and interactivity. Student responses also showed positive perceptions of accessibility, visual attractiveness, and the effectiveness of the e-LKM in enhancing understanding and learning engagement. Therefore, the case study–based e-LKM is suitable for use as an alternative learning resource in Multicultural Education.